2020
DOI: 10.13057/biodiv/d210608
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite polymorphism for molecular characterization of pomelo (Citrus maxima) accessions from Indonesia

Abstract: Abstract. Susandarini R, Subandiyah S, Daryono BS, Rugayah. 2020. Microsatellite polymorphism for molecular characterization of pomelo (Citrus maxima) accessions from Indonesia. Biodiversitas 21: 2390-2395. Citrus maxima (Burm.) Merr. (pomelo) as a minor fruit crop deserve attention on its phenotypic and genotypic variability to avoid the risk of extinction. Previous study showed that pomelo from Indonesia has high morphological variability, and thus it is interesting to explore its genotypic variability using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Pomelo (Citrus maxima, previously known as Citrus grandis) is a perennial fruit plant that belongs to the Rutaceae family [6]. The naming of this fruit varies in each region, as listed in The pomelo plant is a species of tropical fruit plant originating from Southeast Asia, which yields fruit twice a year.…”
Section: Taxonomy and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Pomelo (Citrus maxima, previously known as Citrus grandis) is a perennial fruit plant that belongs to the Rutaceae family [6]. The naming of this fruit varies in each region, as listed in The pomelo plant is a species of tropical fruit plant originating from Southeast Asia, which yields fruit twice a year.…”
Section: Taxonomy and Morphologymentioning
confidence: 99%
“…The pomelo plant thrives in tropical lowlands up to an altitude of 400 meters, with an average temperature of 25-32°C and rainfall ranging from 1,500-2,500 mm, accompanied by a dry period of 3-4 months. Its fruit is large and round, with a diameter of 10-30 cm, consisting of thick skin (flavedo as the outer skin and albedo as the inner skin), which makes up 30% of its weight, and its flesh is pink or white with a sweet, bland, or sweet-tart taste [3,[6][7][8][9]. The picture of pomelo is shown in Figure 1.…”
Section: Taxonomy and Morphologymentioning
confidence: 99%
“…The SSR sequences amplified using mCaCIR002 primers in this study showed high variability in the number of (CT)n repeats representing microsatellite polymorphism become strong evidence on the intraspecific variability in C. asiatica. Previous studies showed that microsatellites polymorphism caused by mutations can be used as genetic markers for evolutionary studies, phylogenetic analysis, gene flow, paternity analysis, and population structure analysis (Milner et al 2013;Mehrotra and Goyal 2014;Putman and Carbone 2014;Vieira et al 2016;Susandarini et al 2020).…”
Section: Variation In Microsatellite Repeat Numbermentioning
confidence: 99%
“…Pomelo (Citrus maxima) are potential plants to be developed in Indonesia, the production center of Pomelo South Sulawesi is Pangkep Regency [1] which contributes more than 80% of production [2]. South Sulawesi's contribution nationally to the supply of Pomelo ranks first, with 30.76%.…”
Section: Introductionmentioning
confidence: 99%